2017
DOI: 10.1016/j.healthplace.2017.05.001
|View full text |Cite
|
Sign up to set email alerts
|

Nursing work and sensory experiences of hospital design: A before and after qualitative study following a move to all-single room inpatient accommodation

Abstract: The embodied experience of nursing practice is rarely studied. Drawing on data from an internationally relevant larger study conducted in 2013–14, here we explore the sensory dimension of the embodied experiences of nursing staff working on two acute NHS hospital wards before and after a move to all-single room inpatient accommodation. We undertook a secondary analysis of 25 interviews with nursing staff (12 before and 13 after the move with half [13/25] using photographs taken by participants) from a mixed-me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
101
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 40 publications
(104 citation statements)
references
References 19 publications
2
101
0
1
Order By: Relevance
“…In the English study, the nurses also identified the missed opportunities of informal learning from each other, because of the professional isolation of the single‐room environment (Maben et al, ). Our Australian study noted that the preferred staffing model included both a RN and an EN working together (team nursing), and whilst team nursing may reduce nurses’ feelings of isolation following the move to the single‐room hospital, it might not address the lack of opportunities for informal peer learning identified as reduced in the English study by Donetto, Penfold, Anderson, Robert, and Maben ().…”
Section: Discussionmentioning
confidence: 98%
“…In the English study, the nurses also identified the missed opportunities of informal learning from each other, because of the professional isolation of the single‐room environment (Maben et al, ). Our Australian study noted that the preferred staffing model included both a RN and an EN working together (team nursing), and whilst team nursing may reduce nurses’ feelings of isolation following the move to the single‐room hospital, it might not address the lack of opportunities for informal peer learning identified as reduced in the English study by Donetto, Penfold, Anderson, Robert, and Maben ().…”
Section: Discussionmentioning
confidence: 98%
“…This finding is not a unique feature of the case presented here, but rather reflects an important trade‐off in the healthcare profession, as healthcare facilities continue to transition to single‐patient rooms (Donetto et al . , Maben et al . ).…”
Section: Discussionmentioning
confidence: 99%
“…For example studying nurses in two acute care settings in England, Donetto et al . () similarly described how moving to single‐patient rooms decreased key aspects of teamwork, including the nursing staff's ability to provide and/or access help due to the physical separation that no longer allowed them to see or hear other providers as they worked. While the current study is unable to speak to the clinical outcomes of NICU patients, the decreased collaboration between providers runs contrast to contemporary calls for increased teamwork to improve patient outcomes (Institute of Medicine (U.S.), Committee on Quality of Health Care in America ).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations